Pengaruh Organizational Attraction dan Involvement in Alumni Association terhadap Organizational Identification Alumni Perguruan Tinggi (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the influence of Organizational Attraction and Involvement in Alumni Association on the Organizational Identification of university alumni. Data were collected from 394 alumni of Universitas Kristen Maranatha using a structured questionnaire and analyzed through simple and multiple linear regression using SPSS. The results indicate that both Organizational Attraction and Involvement in Alumni Association have a positive and significant effect on Organizational Identification, both partially and simultaneously. The model explains 22.5% of the variance in alumni organizational identification. These findings support social identity theory and highlight the importance of enhancing institutional reputation and promoting alumni engagement in institutional activities. It is recommended that universities strengthen their organizational attractiveness and develop strategic and meaningful alumni involvement programs. Future studies are encouraged to examine mediating and moderating variables and to broaden the institutional context for greater generalizability